An evaluation of the problems of open range use system in Northern Cameroon - Tedonkeng Pamo, E.; Tedonkeng Pamo, C. (Tropicultura, 1991)
The concept of the "tragedy of the Commons" has been examined within the economic and legal framework. The extent to which this concept has been applied in the sahelian and subsahelian rangelands has been reviewed. An overall evaluation of the range use system in these areas, and especially in North Cameroon, points to the existence of serious discrepancies between the concept and the practical realities. Consequently, these areas can not be referred to as common rangelands, but rather as open access rangelands. Short-comings in the implementation of the internationalization of the open access rangeland costs in the past, provided a basis for the suggestion of guidelines and a procedure as to how this internationalization could presently be successfully implemented in North Cameroon.